2001
DOI: 10.1136/bmj.322.7277.24
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and trends in overweight and obesity in three cross sectional studies of British children, 1974-94

Abstract: Objectives To report trends in overweight and obesity, defined by new internationally agreed cut-off points, in children in the United Kingdom. Design Three independent cross sectional surveys. Setting Primary schools in England and Scotland. Participants 10 414 boys and 9737 girls in England and 5385 boys and 5219 girls in Scotland aged 4 to 11 years. Main outcome measures Prevalence and change in prevalence of overweight and obesity, as defined by the international obesity task force, in 1974, 1984, and 199… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

30
259
8
21

Year Published

2002
2002
2007
2007

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 443 publications
(318 citation statements)
references
References 10 publications
30
259
8
21
Order By: Relevance
“…Girls were more likely to be overweight or obese than boys, as has been observed with other recent UK surveys. These results represent a marked increase from the previous survey conducted in Scotland in 1994, 2 and these data confirm that the previously forecast epidemic is continuing to develop at an exponential rate. When we examined the obesity levels in the higher and lower income groups, we found that the prevalence of obesity was much higher in the lower-income group when compared with the higher-income group (Figure 2a).…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…Girls were more likely to be overweight or obese than boys, as has been observed with other recent UK surveys. These results represent a marked increase from the previous survey conducted in Scotland in 1994, 2 and these data confirm that the previously forecast epidemic is continuing to develop at an exponential rate. When we examined the obesity levels in the higher and lower income groups, we found that the prevalence of obesity was much higher in the lower-income group when compared with the higher-income group (Figure 2a).…”
Section: Resultssupporting
confidence: 87%
“…1 Historically, the UK has lagged behind the US and Canada in the prevalence of obesity and overweight, although recent surveys have shown that the UK is starting to show increases in rates of overweight and obesity, both in the adult population and in children. 1,2 Recent work has shown a corresponding increase in dyslipidaemia and insulin resistance in schoolchildren and the potential for future morbidity in the form of an increased number of individuals with type 2 diabetes and cardiovascular disease. [3][4][5] Here we confirm both the continued increase in childhood obesity in Scotland, its relationship to poverty, and provide a novel analysis of the role of height limitation in obesity.…”
Section: Introductionmentioning
confidence: 99%
“…Less than 1% of the population should be obese, and around 9% overweight by this definition. We found higher rates for overweight (18.9%) and obesity (4.2%), in line with trends from other studies (Reilly & Dorosty 1999;Chinn & Rona, 2001).…”
Section: Validation Of Debq-p In the Italian Population R Caccialanzasupporting
confidence: 93%
“…[9][10][11][12][13][14] The waist circumference measure, a proxy of visceral fat, is uniformly included in the diagnosis of the 'metabolic syndrome' in both children and adults. 99 Safe and effective treatments for central obesity in youth are urgently needed, given the increasing prevalence of overweight in youth, [1][2][3][4][5] and that the prevalence of 'metabolic syndrome' in overweight children and adolescents has been reported to be as high as 29-50%, 10,13 and rising. 100 Numerous studies have found that physically active boys and girls are at decreased risk of metabolic syndrome compared with those less active.…”
Section: Central Obesitymentioning
confidence: 99%
“…[1][2][3][4][5] In adults, the morbidity and mortality burden of obesity is well documented. Of major concern is the growing body of evidence reporting overweight-related morbidity in childhood and adolescence, both in the psychosocial [6][7][8] and physiological domain.…”
Section: Introductionmentioning
confidence: 99%